1983
DOI: 10.1002/jmv.1890120408
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of blood coagulation and complement system in neotropical primates infected with Junin virus

Abstract: The neotropical primate Callithrix jacchus infected with Junin virus presented an acute disease with hematological and neurological manifestations and died 17 to 24 days after infection. This picture is similar to that of human Argentine hemorrhagic fever (AHF). Blood coagulation and complement studies were performed in ten C jacchus animals inoculated with 10(3) TCID50 of Junin virus, the prototype pathogenic XJ strain. Four monkeys were used as normal controls. Infected monkeys and normal controls were bled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 20 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Subcutaneous exposure with 1,000 TCID 50 s of JUNV strain XJ produces signs of illness such as anorexia, decrease in weight, leukopenia, thrombocytopenia, viremia, neurological illness (tremors), and hemorrhage of the gums, pharynx, and esophagus abdominal cavity, in addition to death [ 127 130 ]. A profile of coagulation parameters and complement activity were also reported but are inconsistent with known human disease and other NHP model systems [ 129 ]. However, in general disease in this model is similar to human disease.…”
Section: Arenavirus Animal Modelsmentioning
confidence: 99%
“…Subcutaneous exposure with 1,000 TCID 50 s of JUNV strain XJ produces signs of illness such as anorexia, decrease in weight, leukopenia, thrombocytopenia, viremia, neurological illness (tremors), and hemorrhage of the gums, pharynx, and esophagus abdominal cavity, in addition to death [ 127 130 ]. A profile of coagulation parameters and complement activity were also reported but are inconsistent with known human disease and other NHP model systems [ 129 ]. However, in general disease in this model is similar to human disease.…”
Section: Arenavirus Animal Modelsmentioning
confidence: 99%
“…Therefore, indirect effects might be responsible for the increased vascular permeability seen in patients [30], and the profuse bleeding often seen is presumably a consequence of vascular damage caused by both cytokines and virus replication. Thrombocytopenia, which is commonly found in human patients and animal models, and elevated amounts of factor VIII-related antigen (von Willebrand factor, vWF), which is synthesized and released from endothelial cells, could contribute to the observed endothelial dysfunction [90][91][92][93][94].…”
Section: Pathogenesis Of Old and New World Hemorrhagic Feversmentioning
confidence: 99%
“…The central involvement of coagulopathy in arenaviral disease has been ruled out as there is no general correlation of specific coagulation abnormalities with the severity of disease. Furthermore, there are only four reported observations of disseminated intravascular coagulation (DIC) in AHF cases [74,100], indicating that DIC is not an important pathogenic phenomenon in arenaviral disease, although there are several modest abnormalities of clotting factors and activation of fibrinolysis [90][91][92][93][101][102][103][104]. Studies of JUNV infection have revealed that Factor V is uniformly elevated (starting from day 8), and fibrinogen is normal in mild cases and elevated in severe cases in the later stages of infection (after day 10).…”
Section: Pathogenesis Of Old and New World Hemorrhagic Feversmentioning
confidence: 99%
See 1 more Smart Citation
“…Disseminated intravascular coagulation (DIC) had initially been proposed as the possible primary cause of hemorrhages in this disease (16,17). However, this hypothesis could not be substantia ted by histopathological and laboratory findings, neither in patients nor in experimental models (18)(19)(20)(21). Histological as well as clinical and laboratory evidence of DIC has so far been reported in a single human case (22).…”
Section: Introductionmentioning
confidence: 99%